Draconarius exilis, a new species of coelotine spider from China (Araneae, Amaurobiidae) - Zhang, Zhi-Sheng; Zhu, Ming-Sheng; Wang, Xin-Ping (Zootaxa, 2005)
A new species of Draconarius, D. exilis sp. nov., from China is described. The species has close affinities to D. incertus Wang, 2003 (= D. parabrunneus Wang, 2003, new synonymy) and D. pseudobrunneus Wang, 2003 forming the newly proposed incertus-group of Draconarius. Species of this group share the following characters: the absence of epigynal teeth, the wrinkled anterior atrium of epigynum, the small and anteriorly extended spermathecae of female, and the short cymbial furrow (less than half cymbial length), the short embolus, the prolaterally originated, bifurcated conductor, and the simple, non spoon-shaped median apophysis.